Aksjonsforskning i Norge, volum 2 Grunnlagstenkning, forskerroller og bidrag til endring i ulike kontekster - Gjøtterud, Sigrid; Hiim, Hilde; Husebø, Dag; Jensen, Liv Helene (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2020)
"The purpose of this anthology is to show different perspectives on epistemology, research roles and contexts in action research. Contributors are researchers who have extensive experience in combining practice development and knowledge development in action research projects. Several of the articles focus on the epistemological and methodological basis of action research and dilemmas related to the role of the researcher. Questions concerning the purpose of action research, methods of change, and what kind of knowledge is to be developed by and for whom are discussed. Some of the articles explore challenges that are about fundamental values, power, democracy, and dialogue in action research. The articles also provide examples of how action research can be carried out in different contexts. Some articles are about researching your own practice, possibly with colleagues, students or other partners. There are also examples that show how researchers at universities are invited into ongoing research work e.g. in schools, health institutions, local communities or companies. The researchers contribute in various ways to facilitate the development process, with professional input, and with documentation. Combining development and research, regardless of context, requires researchers to explain their position, and in collaboration with the participants clarify what roles or functions the participants should have and what is the goal of the development and research. An important issue in the anthology is to point out that action research as collaborative research will necessarily involve dilemmas related to power, values and different views on knowledge. We hope that the anthology will help to raise awareness of such dilemmas."